2006
DOI: 10.1007/s00431-006-0139-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasma antithrombin III and protein C levels in early recognition of late-onset sepsis in newborns

Abstract: We concluded that the measurement of plasma ATIII and, especially, PC levels may facilitate the recognition of sepsis and, with respect to PC, may have a prognostic value. Plasma PC functional concentration below 10% might be the indication for supplementation of PC concentrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 10 publications
2
17
0
3
Order By: Relevance
“…Recently published studies established low plasma PC activity levels as an independent risk factor for death in low birthweight neonates (3,4), a fact which was described in adults previously (17). According to this data, the preintervention PC plasma activity in the patients reported here had a risk of dying of approximately 80%; alternatively, the NEOMOD score gives this risk as approximately 70%.…”
Section: Patient Characteristicsmentioning
confidence: 71%
“…Recently published studies established low plasma PC activity levels as an independent risk factor for death in low birthweight neonates (3,4), a fact which was described in adults previously (17). According to this data, the preintervention PC plasma activity in the patients reported here had a risk of dying of approximately 80%; alternatively, the NEOMOD score gives this risk as approximately 70%.…”
Section: Patient Characteristicsmentioning
confidence: 71%
“…Several studies have reported that plasma levels of antithrombin and protein C are significantly lower in patients with poor prognosis [3-5]. However, these results were based on a relatively small number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, antithrombin and protein C deficiency are common in DIC patients with poor prognosis [4, 5]. Therefore, plasma levels of natural anticoagulants can be used in the diagnosis and prognosis of DIC.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a shift towards inactivation of protein S and depletion of anticoagulant proteins including antithrombin III (ATIII) and protein C167, 168. A small study demonstrated low protein C levels in preterm neonates with sepsis predicted death169.…”
Section: Pathophysiology Of Sepsis and Shock:molecular And Cellular Ementioning
confidence: 99%